Comparing active teaching to hybrid lecture-based method for learning radiology basics: A single center controlled study - Fabien de Oliveira; Jean-Paul Beregi; Hugo Potier; Thorgal Brun; Chris Serrand; Julien Frandon (Research in Diagnostic and Interventional Imaging)
Objective: There is a lack of knowledge about radiology among medical students at the start of their curriculum. The optimal teaching method for radiological basics remains uncertain. We conducted a controlled trial to compare the effectiveness of full active learning and hybrid lecture-based teaching methods. Methods: All second-year medical students at Nîmes University Hospital (Nîmes, France) were invited to participate in a training session in the radiology unit. Volunteers were divided into hybrid lecture-based and full active learning groups. The hybrid lecture-based group received a lecture-based session followed by a unit visit, while the full active learning group utilized a structured form with progressive objectives during the visit. Pretests, immediate post-tests, and two-week follow-up tests were conducted. Short-term progression was the primary outcome, with secondary objectives including mid-term acquisition and associated factors. Results: 51 students participated, with 20 in the hybrid lecture-based group and 31 in the full active learning group. Both groups exhibited significant progression between the first and second tests (+8.48 and +2.52 respectively, p < 0.01). The hybrid lecture-based group showed significantly greater mean progression (p < 0.01). Mid-term results indicated score decrease particularly in the hybrid lecture-based group, but it still maintained significantly superior performance (15.02/20 versus 12.33/20 for full active learning group, p < 0.01). Conclusion: The hybrid pedagogical method yielded superior results in teaching second-year medical students the basics of radiology compared to the full active learning teaching method.